Pengaruh Model Penemuan Terbimbing Berbantuan WEB Terhadap Keterampilan Berpikir Kritis Matematis Siswa Kelas X - Lalu Irfan Abdul Manaf; Nyoman Sridana; Arjudin Arjudin; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2021)
The background of this research is, there is no learning model that can optimally support critical thinking skills, so it takes an innovative learning model. In this case, the researchers used web helped to guide discovery learning model to improve the critical thinking skills of the student in class X SMAN 4 Praya in academic year 2019/2020. This study aimed to find an effect of web assisted guided discovery learning on trigonometry material to critical thinking ability of the student in class X SMAN 4 Praya in academic year 2019/2020. This study use a quantitative research approach to the type of experimental research. In this experiment the researchers used a quasi-experimental, and uses two classes as a research, the experimental class and control class. The population of this research is all the student in class X SMAN 4 Praya and and choose two class as a sample class that is X MIPA 5 as a experimental class and X MIPA 3 as control class. Student in experimental class used web assisted guided discovery learning model and in control class used guided discovery without web assisted. The result of the research showed that the average of critical thinking ability in the experimental class is better than control class which is in the experimental class is in the less effective category and control class in ineffective category.